A Virtual Lab Activity Combined with a Prediction-Observation-Explanation Model to Improve Students Learning Outcomes in Direct Current Circuit - Zega, Adifeti; Hartanto, Theo Jhoni; Budi, Gunarjo Suryanto (Jurnal Pendidikan MIPA, 2023)
Laboratory activities are very important in the process of teaching and learning physics in schools. Limited laboratory facilities in schools are enough to hinder direct laboratory activities. The combination of predict-observe-explain (POE) learning with virtual laboratory activities can be an alternative to developing a more active, interesting, and meaningful physics learning process and overcome the limitations of equipment in the laboratory. This study aims to describe virtual lab activities with POE learning on student cognitive learning outcomes in direct current circuit topics. Participants were taken from senior high school students in the 12th grade in Palangka Raya, Indonesia. It includes 30 students who have not yet studied direct current circuits. A pre-experimental research method with a one-group pre and post-test design was used. The finding indicates that students cognitive learning outcomes were increased with a medium category (N-Gain score 0.69). Specifically, the increase was found in the subtopics electric current and potential difference (N-Gain score 0.66), simple direct current circuits (N-Gain score 0.68), electrical circuits series and parallel (N-Gain score 0.73), and Ohm's Law (N-Gain score 0.70). Based on this research, virtual-lab activity with POE learning could be considered an alternative to conducting a meaningful learning activity, especially in physics learning.Keywords: crocodile physics, direct current, physics, POE learning model, virtual lab.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp309-320